Are there returns to experience at low-skill jobs? Evidence from single mothers in the United States over the 1990s - Adam Looney; Dayanand S. Manoli (W.E. Upjohn Institute for Employment Research, 2016)
Policy changes in the United States in the 1990s resulted in sizable increases in employment rates of single mothers. We show that this increase led to a large and abrupt increase in work experience for single mothers with young children. We then examine the economic return to this increase in experience for affected single mothers. Despite the increases in experience, single mothers' real wages and employment have remained relatively unchanged. The empirical analysis suggests that an additional year of experience increases single mothers' wage rates by less than 2 percent, a percentage lower than previous estimates in the literature.
Keywords: J31; I38; J12; J24; 330; Wage returns to experience; Welfare reform; Personal Responsibility and Work Opportunity Reconciliation Act (PRWORA) of 1996; Single mothers; Low-skill labor; Current Population Survey; Synthetic cohorts